Scott and Amundsen - Honda, Katuiti (The Asahi-Shinbun, 1999)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Miljøgifter og radioaktivitet i norsk fauna : inkludert Arktis og Antarktis - Knutzen, Jon; Fjeld, Eirik; Hylland, Ketil; Killie, Barbro; Kleivane, Lars; Lie, Elisabeth; Nygård, Torgeir; Savinova, Tatiana; Skåre, Janneche Utne; Aanes, Karl Jan (Direktoratet for naturforvaltning, 1999)
Keywords: Antarktis; dyreliv; forurensning; miljøgifter; polarområdene; radioaktivitet; toksikologi; zoologi

Noruega y las regiones polares - Hansson, Rasmus (Real Ministerio Noruego de Asuntos Exteriores, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norvegija i poljarnye rajony - Hansson, Rasmus (Izdano Ministerstvom inostrannych del Norvegii, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norwegen und die Polargebiete - Hansson, Rasmus (Kgl. Norwegisches Ministerium für Auswärtige Angelegenheiten, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

The effects of personality and interpersonal relations on crew performance during space simulation studies - Sandal, Gro Mjeldheim (Life Support & Biosphere Science, 1998)
There has been a substantial increase in the number of people living and operating in isolated, confined, and artificially engineered environments, such as spacecraft, deep diving, weather stations, submarines, and polar outposts. This article gives an overview of research undertaken in a variety of extreme environments in an effort to better understand how semiautonomous, task-oriented groups operating within these environments develop over time, as well as identification of the individual characteristics that promote performance under such circumstances. Research reviewed includes space simulation studies for the European Space Agency (ESA) where groups were isolated in hyperbaric chambers, as well as findings from polar expeditions, space missions, submarine missions, and other military settings. Findings from the space simulation studies in hyperbaric chambers provided empirical evidence for interpersonal issues anecdotally reported in Antarctica and in other isolated, operational team environments, such as "scapegoating" of deviant crew members, displacement of aggression to outside personnel, and time patterns in psychological reactions. No indications of a "psychological limit" for how long people can tolerate remaining in isolation and confinement were found. Certain personality characteristics were consistently associated with coping, and individuals characterized by strong achievement motivation combined with interpersonal sensitivity seemed to adapt better than others. Together, these results have implications for selection and training of people operating within extreme environments.
Keywords: Antarktis; polarekspedisjoner; polarforskere; polarområdene; psykologi

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Strategi for norsk forskning i Antarktis - forskningsråd, Norges (Norges forskningsråd, 1997)
Keywords: Antarktis; Antarktistraktaten; Norge; forskning; forvaltningsansvar; miljøendringer; polarområdene

Dagboksnotater fra Sydpolen - Hassel, Sverre (Vågemot miniforl., 1997)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Governing the Antarctic : the effectiveness and legitimacy of the Antarctic Treaty System - Støkke, Olav Schram (ed.); Vidas, Davor (ed.) (Cambridge University Press, 1996)
Keywords: Antarktis; Antarktistraktaten 1959; internasjonal politikk; polarområdene; politikk

Background to the establishment of Norsk Polarinstitutt : postwar scientific and political agendas - Friedman, Robert Marc (Umeå university, 1995)
Keywords: Antarktis; Norsk Polarinstitutt; historie; internasjonal; polarområdene; politikk

Moje życie polarnika - Amundsen, Roald; Thylwe, Halina (Iskry, 1993)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Environmental radioactivity in the Arctic and Antarctic - Holm, Elis (red.); Strand, Per (red.) (Scientific Committee of the International Conference on Environmental Radioactivity in the Arctic and Antarctic, 1993)
Keywords: Antarktis; miljøforurensing; polarområdene; radioaktivitet

The Antarctic treaty system in world politics - Jørgensen-Dahl, Arnfinn (Red.); Østreng, Willy (Red.) (Macmillan in association with The Fridtjof Nansen Institute, 1991)
Keywords: Antarktis; Antarktistraktaten; forvaltning; havrett; internasjonalt samarbeid; miljø; naturressurser; polarområdene; politikk; ressurser; rett

Perspektiver for norsk forskning i Antarktis : langtidsplan for norsk Antarktis-forskning, høringsutkast av kapittel 6: framtidig norsk forskning - Omholt, Anders; Nygard, Jarle (Nasjonal komite for miljøvernforskning, NAVF, 1991)
Keywords: Antarktis; Norge; glasiologi; klima; marinøkologi; miljøforskning; polarforskning; polarområdene

Adaptations to alpine and polar environments in insects and other terrestrial arthropods - Sømme, Lauritz; Block, William (Insects at low temperature, 1991)
Keywords: Antarktis; ekspedisjoner; insekter; kuldetoleranse; polarområdene; virvelløse dyr

Nankyoku ten - Amundsen, Roald; Nakada, Osamu (Dorufin Press, 1990)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Bibliographia Phytosociologica. Norwegian possessions in the polar regions - Sunding, Per (Excerpta botanica, Sectio B, 1990)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; bibliografi; botanikk; polarområdene